Yugoslavia, the former and future reflections by scholars from the region (Brookings Inst. [u.a.], 1995)
This book contains an unprecedented collection of essays written by scholars from the former Yugoslavia, exploring the events that led to the devastating disintegration of their homeland. The scholars, who were selected from the different, groups now in conflict, provide insightful, multicultural perspectives on the crisis.